The dependence between interdisciplinarity and discipline concepts - Neves , Cleuler Barbosa das (Seven Editora, 2023)
The conceptualization of interdisciplinarity’s problem presupposes the concept of discipline, as to break this paradigm, as to understand that one cannot think of him without the knowledge of the various disciplines that contribute to the understanding of complex research’s objects, like, for example, the environment and its diversified ecosystems. The goal is to present a synthetic concept of interdisciplinarity from a literature search by use of the argumentation dialectical method, being inexorable, for this, return to both concepts of discipline and multidisciplinary. DOI:https://doi.org/10.56238/sevened2023.006-068